Ecologies of intermediation and the Social and Solidarity Economy: A new form of governance for ecological transitions - Olaizola Alberdi, Jon; Bollain, Julen; Herce-Laceta, Beñat (Cooperativismo & Desarrollo, 2025)
This article argues that ecological transitions are increasingly shaped by overlapping intermediaries and that Social and Solidarity Economy (SSE) principles can make these “ecologies of intermediation” more effective and fair. Using an exploratory integrative literature review of core work on intermediation ecologies and 13 studies linking SSE to eco-social transitions, the authors identify coordination problems and SSE-based responses. They show how intercooperation, democratic network governance, territorial embeddedness and mission-oriented ethical finance can transform competition for resources into complementarity, distribute sensing and decision-making across scales, and sustain long-term transition work beyond short project cycles. From this analysis, the article develops a conceptual framework and testable propositions and proposes policy guidance that recognizes SSE networks as ecology-level stewards, designs hybrid arenas where public, regime and community intermediaries co-decide, builds capabilities for value-based cooperation and revises evaluation systems to capture relational and value outcomes.